Adaptive Learning Strategies Using Technology in German Schools - Fischer, Claudia; Koch, Sebastian; Richter, Laura (Journal Emerging Technologies in Education, 2025)
Background. The increasing integration of technology in education has transformed teaching and learning practices across the globe. In Germany, adaptive learning strategies have gained traction as personalized approaches to meet diverse student needs. However, the effectiveness of these strategies, particularly when combined with technological tools, remains an area of active research. Purpose. This study aims to explore the implementation of adaptive learning strategies using technology in German schools. The research focuses on understanding how these strategies impact student engagement, performance, and individualized learning outcomes. Method. A mixed-methods approach was employed, combining quantitative data from student performance assessments and qualitative insights from teacher interviews. A total of 200 students across five German schools participated in the study, using adaptive learning platforms designed to personalize educational content. Teachers were interviewed to assess their experiences with these tools and strategies. Result. The findings suggest that adaptive learning strategies enhanced student engagement and performance, with significant improvements in individualized learning outcomes. Students who interacted with technology-driven adaptive platforms showed increased motivation and better retention of subject matter compared to those in traditional learning environments. Teachers reported positive experiences, noting that the strategies allowed for more tailored support for students. Conclude. The integration of adaptive learning strategies using technology has shown positive effects on student learning outcomes in German schools. These findings suggest that further adoption and refinement of such strategies can play a key role in fostering personalized education.